Investigation on possible causes of expansion damages in concrete – a case study of sleepers in Indian Railways - Awasthi, Anupam; Matsumoto, Koji; Nagai, Kohei; Asamoto, Shingo; Goto, Seishi (Journal of Asian Concrete Federation, 2017)
Indian Railways uses factory made pre-tensioned pre-stressed concrete sleepers for its track. These sleepers start cracking after 6-9 years of their manufacturing in many areas of the Indian Railways. For the investigation of the premature cracking of sleepers, different categories of samples namely “Severely damaged”, “Moderately damaged”, and “Undamaged” are collected from different locations of Indian Rail- ways. These samples are analyzed under Scanning Electron Microscope (SEM) and Energy Dispersive Spec- troscopy (EDS). SEM images reveal that there is large ettringite deposition at the interfaces of aggregate and paste in case of “Severely damaged” and “Moderately damaged” sleepers, which could be a cause of delete- rious expansion and subsequent cracking, whereas the interfaces of “Undamaged” sleepers were found to be intact. High temperature experienced by these sleepers in form of steam curing during their production in factories may lead to Delayed Ettringite Formation (DEF) and subsequent expansion and cracking. Tempera- ture recorded in the concrete sleeper plant during steaming of the sleepers reveals that the temperature inside concrete exceeds 80°C, which is a critical temperature for the occurrence of damage due to DEF in future. Also, stress bench method of production of concrete sleepers, used in Indian Railways for older concrete sleeper plant, poses some structural deficiency which adversely affects the temperature of curing. Thus, DEF could be the possible cause of premature cracking of sleepers in Indian Railways.